O vocabulário ornamental de Antônio José Landi: um álbum de desenhos para o Grão Pará - OLIVEIRA, Domingos Sávio de Castro (Universidade Federal do Pará, 2015)
The architecture of the city of Belém, in Pará, in the second half of century XVIII is marked by the works of the Italian architect Antônio José Landi responsible for the project and construction, or remodels, of buildings that mark the landscape of the city until the current days. Analyzing the published bibliography regarding the artist, it is possible to notice a fluctuation between the authors in what says about the classification of his artistic style. It is possible to attribute this fact to the influences suffered by the architect throughout his formation in Europe, what printed in his language elements of some artistic chains. It’s objective of this work, through a systemize study of the ornament used for the architect, to perceive his ornamental vocabulary and to supply then beddings studies regarding the influences that the workmanship of Landi can have provoked in the local art. For in such a way, the ornates had been congregated in four groups in order to facilitate the visualization of his vocabulary and his ornamental language. Vast was his production between Italy, Portugal and Brazil, however, had been prioritized the ornaments used in the workmanship carried through in Brazilian lands, its characteristics, its use and its variations. The applied methodology consisted in bibliographical research, survey and analysis of the drawings carried through in Brazil and photographic register and analysis of the workmanships executed in Belém. To the end of the research, it is concluded that the Italian artist developed his art, with the use of an ornamental vocabulary formed by the artistic influences suffered by him in the Europe and of the conditions of the Amazonian environment, its limitations of materials and manpower.